UNDERSTANDING IDEA OF CURRICULUM 2013 AND ITS CONSISTENCY ON DEVELOPING CURRICULUM DOCUMENT AT LEVEL OF EDUCATION UNIT (KTSP) AT PRIMARY SCHOOL LEVEL - Prihantini, Prihantini (Universitas Pendidikan Indonesia, 2018)
Abstract:. This study is based on various issues of Curriculum 2013, both in terms of teacher readiness to accept the Curriculum 2013, an understanding of the idea of Curriculum 2013, as well as in the implementation of teaching and learning. In the curriculum development theory, curriculum ideas are an important component that the curriculum development team needs to understand, so that the development of curriculum documents composed reflects continuity with curriculum ideas. The purpose of this study is to describe and explore the understanding of principals and teachers about the idea of Curriculum 2013 and its consistency on developing Education Unit Level Curriculum (KTSP) at elementary school in Sukalarang sub-district, Sukabumi regency. The research method applied is qualitative research with descriptive exploratory approach. The conclusions of the study are: (1) the understanding of principals and teachers about the idea of theÂ Curriculum 2013 at the know stage, the understanding that curriculum ideas have consistency in the development of the Education Unit Level Curriculum (KTSP) document is not yet owned; (2) the development of KTSP document shows no consistency between the idea of Curriculum 2013 with the documents of Book I KTSP, Book II KTSP, and Book III KTSP; (3) the problems faced by school principals and teachers in relation to the Curriculum 2013 is assessment of learning, both with regard to the techniques and types of assessment and techniques of administering the results of the assessment.Recommendations are proposed to policy makers that training strategies need to be changed from